Local party organizations 1985 - Bjurulf, Bo; Håkansson, Anders (Lund University, 2020)
This study was conducted in connection with the 1985 election. The mail questionnaire was directed toward the chairmen of local party organizations and leaders of the local election campaign within a sample of 50 municipalities and three big cities, Stockholm, Göteborg and Malmö. The questions dealt above all with the local organization of the political parties, activities and attitudes and also with election campaigns, election results etc.

Studien genomfördes inför valet 1985 som en enkätundersökning med kommunala partiorganisationer riktad till organisationernas ordförande och valledare. Frågorna handlade framförallt om partiernas kommunala organisation, verksamhet och ställningstaganden. Ett antal frågor utgör en uppföljning av kommunaldemokratiska forskningsgruppens undersökning vid valet 1979. Enkäten var därutöver speciellt inriktad på frågor om partiernas valkampanjer, valresultat etc.
Kommunal partiorganisation 1985
Keywords: local government elections; kommunalval; political parties; politiska partier; election campaigns; valkampanjer; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap